A different approach for the analysis of grapes: Using the skin as sensing element. (May 2018) - Muñoz, Raquel; García-Hernández, Celia; Medina-Plaza, Cristina; García-Cabezón, Cristina; Fernández-Escudero, J.A.; Barajas, Enrique; Medrano, Germán; Rodriguez-Méndez, María Luz
Abstract: In this work, an alternative method to monitor the phenolic maturity of grapes was developed. In this approach, the skins of grapes were used to cover the surface of carbon paste electrodes and the voltammetric signals obtained with the skin-modified sensors were used to obtain information about the phenolic content of the skins. These sensors could easily detect differences in the phenolic composition of different Spanish varieties of grapes ( Mencía, Prieto Picudo and Juan García ). Moreover, sensors were able to monitor changes in the phenolic content throughout the ripening process from véraison until harvest. Using PLS-1 (Partial Least Squares), correlations were established between the voltammetric signals registered with the skin-modified sensors and the phenolic content measured by classical methods (Glories or Total Polyphenol Index). PLS-1 models provided additional information about Brix degree, density or sugar content, which usually used to establish the harvesting date. The quality of the correlations was influenced by the maturation process and the structural and mechanical skin properties. Thus the skin sensors fabricated with Juan García and Prieto Picudo grapes (that showed faster polyphenolic maturation and a higher amount of extractable polyphenols than Mencía ), showed good correlations and therefore could be used to monitor the ripening. Graphical abstract: Highlights: Electrochemical carbon paste sensors based on grape skins have been developed. Correlations with the phenolic content have been established. Phenolic maturation can be monitored from the voltammetric responses. The quality of the correlations depends on the skin properties.